Grundsatz und Norm in der richterlichen Fortbildung des Privatrechts Rechtsvergleichende Beiträge zur Rechtsquellen- und Interpretationslehre - Esser, Josef (Mohr Siebeck, 1990)
Principle and Norm in the Judicial Development of Private Law. Comparative Law Contributions to the Doctrine of Legal Sources and Interpretation.
PublicationDate: 20220812
Keywords: Privatrecht -- Methode -- Grundsatz -- The European Succession Regulation -- Allgemeines -- Array